Genre-based automated writing evaluation for L2 research writing : from design to evaluation and enhancement - Cotos, Elena, 1973- (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2014)
'The craftsmanship of research writing is central to the world of research and academia, but it presents great challenges to novice scholars, especially to L2 writers. This book presents a compelling reinforcement to L2 research writing pedagogy, drawing on a fertile landscape of theoretical and operational frameworks. It offers a model for designing and evaluating a prototype of innovative genre-based automated writing evaluation (AWE) technology, which analyzes research article discourse and generates discipline-specific feedback based on the rhetorical conventions of this genre. Relying on empirical evidence and theoretical rationales, the author discusses the transformation of this prototype into a complete AWE program for L2 research writing. This book will be essential reading for teachers of research writing, researchers of computer-assisted language learning (CALL) and English for academic purposes (EAP), developers of intelligent writing technologies, and any scholars who struggle with the conventions of research writing'--
Machine generated contents note: -- Foreword by Carol A. Chapelle -- Introduction -- PART I: DESIGNING GENRE-BASED AWE FOR L2 RESEARCH WRITING -- 1. Learning and Teaching Challenges of Research Writing -- 2. Automated Writing Evaluation (AWE) -- 3. Conceptualizing Genre-based AWE for L2 Research Writing -- 4. Prototyping Genre-based AWE for L2 Research Writing: The Intelligent Academic Discourse Evaluator (IADE) -- PART II: IMPLEMENTING AND EVALUATING GENRE-BASED AWE FOR L2 RESEARCH WRITING -- 5. Exploring the IADE Genre-based Prototype -- 6. Evaluating the IADE Genre-based Prototype -- 7. From Prototyping to Principled Practical Realization -- Conclusion: Glimpse into the Future.
Includes bibliography (pages 252-281) and index.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Evaluation; Report writing -- Study and teaching (Higher) -- Evaluation; Academic writing -- Study and teaching (Higher) -- Evaluation; English language -- Study and teaching (Higher) -- Foreign speakers -- Evaluation; Interdisciplinary approach in education